Comparison of Rheological, Microstructural, and Textural Properties of Set-Type Yogurts Fermented With Novel Streptococcus thermophilus Strains From Yogurts Produced Mountain Villages of Turkey With Those Produced With Commercial Cultures - Denktas, Begum; Ozturk, Hale Inci; Demirci, Talha; Satilmis, Meryem Kubra; Akin, Nihat (WILEY, 2025)
In recent years, many consumers prefer artisanal cultures as they provide special characteristic taste and flavor compared to commercial ones. Therefore, it is important to preserve traditional cultures and use them in production to reduce dependence on commercial cultures and to develop consumer-pleasing products. This study aimed to evaluate the technological performance of Streptococcus thermophilus strains isolated from yogurts collected from villages in Konya province, and to assess their suitability for commercial yogurt production. Physicochemical, microbiological, textural, rheological, microstructural, and sensory properties of experimental samples were analyzed for 28 days. During the refrigerated time at 4 degrees C, S. thermophilus counts varied between 8.41 and 9.94 log CFU/g. The impact of different S. thermophilus isolates on textural properties was evident, with yogurt samples C, D, and B exhibiting the best performance across all textural parameters. The same situation was observed for microstructure; C, D, and E had the best microstructure images, supported by high water retention capacity and low syneresis degree. B yogurt received the highest general acceptability scores across all storage periods. The results suggested that the strains 10K1, 10K2, and 4K6 could be recommended as potential starter cultures for commercial yogurt production. Novel cultures do not always achieve the flavor and product-specific quality characteristics that consumers like. However, it is very promising that some S. thermophilus strains isolated in this study show better properties than commercial cultures.
Keywords: LAB; rheology; S. thermophilus; texture; yogurt; PROBIOTIC VIABILITY; ACID; IDENTIFICATION; STABILITY; POMACE; Food Science & Technology